2017
DOI: 10.1186/s12933-017-0579-6
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase associated lipocalin (NGAL) is elevated in type 2 diabetics with carotid artery stenosis and reduced under metformin treatment

Abstract: BackgroundNeutrophil gelatinase-associated lipocalin (NGAL), an acute phase protein released by neutrophils, has been described as biomarker of inflammatory states. Type 2 diabetes mellitus (T2DM) is characterized by increased inflammation and an elevated risk for embolization of carotid artery stenosis (CAS). We aimed to explore the role of NGAL systemically and in plaques of diabetics undergoing carotid endarterectomy. Moreover, the potential anti-inflammatory effect of metformin on NGAL was addressed in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 51 publications
3
25
2
1
Order By: Relevance
“…Similarly, Wang et al observed significantly higher circulating NGAL levels in obese people than non-obese people in a Hong Kong population. Moreover, elevated NGAL levels in serum and plaques were associated with type 2 diabetes mellitus in patients with carotid artery stenosis [ 23 ]. Based on these findings, circulating NGAL levels were associated with metabolic diseases, including obesity [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang et al observed significantly higher circulating NGAL levels in obese people than non-obese people in a Hong Kong population. Moreover, elevated NGAL levels in serum and plaques were associated with type 2 diabetes mellitus in patients with carotid artery stenosis [ 23 ]. Based on these findings, circulating NGAL levels were associated with metabolic diseases, including obesity [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, metformin has been shown to reduce neutrophil count in young women with PCOS ( 108 ) and in girls born small for gestational age with exaggerated adrenarche and precocious pubarche ( 108 ), two conditions characterized by a pronounced systemic inflammatory state. Finally, in diabetic patients undergoing endarterectomy for carotid artery stenosis, Eilenberg et al ( 109 ) demonstrated that metformin treatment was associated with reduced expression of neutrophil gelatinase-associated lipocalin—a protein released by activated neutrophils and associated with atherosclerotic plaques vulnerability—thus contributing to lower cerebral embolization events.…”
Section: Effects Of Metformin On Immune Cells Involved In Autoimmune mentioning
confidence: 99%
“…Supporting this finding, Hemdahl AL et al [28] showed that LCN-2 expression was increased in atherosclerotic plaques. Eilenberg W et al [27] also showed that diabetics under metformin treatment had significantly lower LCN-2 levels compared to non-diabetics. We only found that LCN-2 levels were lower in diabetic patients with better glycemic control compared to those with worse glycemic control based on hba1c (hba1c ≤7% vs. >7%) (p = 0.045).…”
Section: Discussionmentioning
confidence: 96%